The effects of x-ray radiation on the eye development of zebrafish. (October 2014) - Zhou, R; Si, J; Zhang, H; Wang, Z; Li, J; Zhou, X; Gan, L; Liu, Y
The toxic effects of x-ray radiation on eye development was measured using zebrafish as a model organism. Zebrafish embryos at 8 h post-fertilization (hpf) were irradiated using X-rays at doses of 1, 2, 4, and 8 Gy. At 24 and 48 hpf, x-ray radiation induced a significant increase in reactive oxygen species (ROS) content and cell apoptotic signals. Both of these increases were dose dependent and there were significant positive relationships between them at 24 hpf. At 48 and 72 hpf, the increase of ROS concentration can be eliminated by increasing activities of superoxide dismutase and catalase. Although the ROS generated by x-ray radiation caused a significant increase in cell apoptosis at 24 and 48 hpf, the cellular layers of the retina and lens formation in the irradiated groups were not significantly disrupted at 144 hpf compared with the control group, with the exception of a heterogeneous distribution of the cells in inner nuclear cell layer and a significant decrease in the diameters of whole eyes after 8 Gy irradiation. X-Ray radiation at later stages of gastrulation may not cause distinct optic complications; however, there is still a risk of microophthalmia at high doses of irradiation.